Analysis of Street Vendor Relocation Policy at Gajah Mada Culinary Center Sidoarjo - Safitri, Eva Nirmala Oky; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2020)
Informal Trader Development Section of the Sidoarjo Disperindag, Coordinator of the PKL area of ​​the Gajah Mada culinary center, members of the PP Satpol, Security at the Gajah Mada culinary center. The analysis technique in this study is a qualitative analysis type, referring to the theory of Miles and Huberman. The results showed that, the analysis of the relocation policy at the Gajah Mada Culinary Center Sidoarjo includes planning starting with the construction of this new building for the relocation of street vendors in accordance with the Sidoarjo Perbup Number 84 of 2017. Organizing aspects through guidance carried out by the Sidoarjo Regency government through the Disperindag and assisted by the Satpol PP. In the aspect of Actuating the Department of Industry and Trade and the Satpol PP of Sidoarjo Regency as the executor and involving other agencies in controlling street vendors and controlling aspects, namely the supervision of the PKL relocation process is going well. Supporting factors include the existence of clear regulations related to the relocation policy of street vendors starting from the Perbup, and Regional Regulations, managed and synergized with several parties so as to be able to make the program a success. While the inhibiting factors include the lack of maintenance and management of culinary centers, less sales and less buyers. and Evaluations that have not been implemented. Keywords: Public Policy, Relocation, Street Vendors